Anthropogenic Blastocystis from Drinking Well and Coastal Water in Guinea-Bissau (West Africa) - Sara Gomes-Gonçalves; Ana Machado; Adriano Bordalo; João R. Mesquita (Microorganisms)
This study provides the first comprehensive investigation of Blastocystis sp. contamination in the drinking well and coastal water sources in Guinea-Bissau, a region grappling with severe water quality challenges. Of the forty-five water samples analyzed (34 well and 9 coastal water sources), Blastocystis sp. was detected in five (11%, 95% CI: 3.71–24.05) of the wells, which serve as a critical and primary drinking source for local communities. The detection of human-associated Blastocystis sp. subtype (ST)2 and ST3 raises concerns about the potential of fecal contamination as a transmission route for Blastocystis sp., underscoring the public health risks associated with an inadequate WASH (water, sanitation, and hygiene) infrastructure. These findings highlight the urgent need for improved water management and further research on waterborne parasitic infections in resource-limited settings.